Physicians and immigrant patients. Cross-cultural communication. - Cave, A. (College of Family Physicians of Canada, 1995)
OBJECTIVE: To formulate recommendations for facilitating communication and helping prevent misunderstandings during cross-cultural patient-physician interactions. DESIGN: Qualitative study using content and semantic analyses of information supplied in focus groups. SETTING: All family physician respondents were associated with departments of family medicine at two urban hospitals and had expressed interest in this study; all immigrant patients were recruited from the English-as-a-Second-Language program at a community agency. PARTICIPANTS: Thirteen immigrant patients, distributed in two groups (one of seven women and one man and one of three men and two women), and five family physicians (two women and three men). MAIN OUTCOME MEASURES: Responses to prepared questions asked in focus groups. RESULTS: Family physicians thought that understanding patients' cultures better would improve quality of care. Patients did not always understand why their physicians asked questions about their culture, sometimes finding these questions irrelevant or intrusive. Comments were used to formulate recommendations for patient-physician interactions. CONCLUSIONS: Physicians and patients are aware of culture as a factor in their relationships but differ on its importance to quality of care.